2020
DOI: 10.1021/acs.est.0c05697
|View full text |Cite
|
Sign up to set email alerts
|

PFAS and Dissolved Organic Carbon Enrichment in Surface Water Foams on a Northern U.S. Freshwater Lake

Abstract: Information is needed on the concentration of per- and polyfluoroalkyl substances (PFAS) in foams on surface waters impacted by aqueous film-forming foam (AFFF). Nine pairs of foam and underlying bulk water were collected from a single freshwater lake impacted by PFAS and analyzed for PFAS by liquid chromatography quadrupole time-of-flight mass spectrometry (LC-QToF) and for dissolved organic carbon (DOC). The DOC of two foam:bulk water pairs was characterized by 1H NMR. Foams were comprised of 16 PFAS with co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
52
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 52 publications
9
52
3
Order By: Relevance
“…Initially, it was suggested that one of the possible sources of PFECHS could be the aviation industry, where it is used as an erosion inhibitor, 70 but additional uses have been identified. 72,73 The PFOS levels found in the Swedish general population in this study (3.6 ng/mL, sum of linear and branched PFOS) were similar to PFOS levels elsewhere in the world (converted to whole blood concentrations): 2.4 ng/mL in the United States, 74 1.4 ng/mL in Germany, 75 and 7.2 ng/mL in China. 76 Nevertheless, this is almost a decade after PFOS and its salts were added to Annex B of the Stockholm Convention, marking them up for restrictions in production and use 77 and additional regulations later on.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Initially, it was suggested that one of the possible sources of PFECHS could be the aviation industry, where it is used as an erosion inhibitor, 70 but additional uses have been identified. 72,73 The PFOS levels found in the Swedish general population in this study (3.6 ng/mL, sum of linear and branched PFOS) were similar to PFOS levels elsewhere in the world (converted to whole blood concentrations): 2.4 ng/mL in the United States, 74 1.4 ng/mL in Germany, 75 and 7.2 ng/mL in China. 76 Nevertheless, this is almost a decade after PFOS and its salts were added to Annex B of the Stockholm Convention, marking them up for restrictions in production and use 77 and additional regulations later on.…”
Section: Discussionsupporting
confidence: 70%
“…While this compound has been detected in various environmental samples before (biota, surface water, and sediment), this is the first time that its widespread occurrence in the general population has been found. Initially, it was suggested that one of the possible sources of PFECHS could be the aviation industry, where it is used as an erosion inhibitor, but additional uses have been identified. , …”
Section: Discussionsupporting
confidence: 68%
“… 17 Fluorinated chain lengths are convenient proxies for expected retention time, but other properties, such as the degree of branching and the charge and hydrophobicity of headgroups, influence retention time as well. 34 , 35 …”
Section: Confidence Criteriamentioning
confidence: 99%
“…Further studies should quantify the ice nucleation properties of other surfactants, many of which exhibit similar properties and behaviors to PFASs in aquatic environments. 115,116 Marine gels, long-chain aliphatic and polymeric molecules that can partition at the air−sea interface, may also form mixtures with PFAS compounds. 117−119 These gels, which can be a source of cloud condensation nuclei in remote marine environments, 120 have also been previously implicated as a potential source of INPs.…”
Section: Atmospheric Implications and Furthermentioning
confidence: 99%
“…Numerous possibilities for additional research exist. Further studies should quantify the ice nucleation properties of other surfactants, many of which exhibit similar properties and behaviors to PFASs in aquatic environments. , Marine gels, long-chain aliphatic and polymeric molecules that can partition at the air–sea interface, may also form mixtures with PFAS compounds. These gels, which can be a source of cloud condensation nuclei in remote marine environments, have also been previously implicated as a potential source of INPs . Although previous studies have characterized the INP activity of organic marine macromolecules, , further research should investigate the ice nucleation of simulated SSA particles containing both macromolecules and PFAS compounds.…”
Section: Atmospheric Implications and Further Researchmentioning
confidence: 99%